CLINICO-PATHOLOGICAL CHARACTERISTICS OF LUPUS NEPHRITIS IN EASTERN ZONE OF INDIA: A SINGLE TERTIARY CENTER EXPERIENCE - Panda, Smaraka R; Kar, Chittaranjan; Sahu, Prasant Kumar; Rout, Sashibhusan; Mohanty, Bishwaranjan; Behera, Tapas Ranjan; Behera, Sudeshna (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Lupus nephritis (LN) is the most common and serious manifestation of systemic lupus erythematosus (SLE) and an important cause of morbidity and mortality. Although diagnosis of LN is straight forward in a patient with SLE and proteinuria, and active urine sediment and perhaps renal insufficiency, still renal biopsies are required at diagnosis to enable classification of nephritis severity, to provide prognostic information, and to guide treatment. Hence, the objective of this study is to determine the frequency of distribution of different classes of LN based on renal biopsy reports and to correlate it with various laboratory findings. Methods: Retrospective study was done in all patients with LN who had at least one representative renal biopsy and evaluated in Nephrology Department of SCB Medical College, Cuttack, in 6-month duration. Various laboratory values were recorded and correlated with histopathological lupus classifications. Results: Out of 35 patients enrolled, 33 (94.28%) were females and 2 (5.71%) were males. Mean age was 27.53Â±12.26 years. Majority of cases belong to Class IV followed by Class V. Patients of Class IV LN have a significantly low hemoglobin level. Similarly, serum urea and creatinine are higher in Group IV than other groups, and serum creatinine was found to be significant. 24 hrs urinary protein excretion has a significant correlation with the classes of LN. Conclusion: This study suggests some meaningful correlation between laboratory findings and histopathological lupus classification. This study also suggests that renal biopsies are still beneficial for better evaluation of renal status and determination of LN classes. Keywords: Clinico-pathological correlation, Lupus nephritis, Biopsy.